Handbook of Internal Migration in India - Rajan, S. Irudaya; M., Sumeetha (SAGE Publications India Pvt Ltd, 2020)
Handbook of Internal Migration in India is an inter-disciplinary, multi-faceted and thought-provoking book on internal migrants and their dynamics among the states in India. The first of its kind, this handbook provides novel information on processes, trends, determinants, differentials and dynamics of internal migration and its inter-linkages with individuals, families, economy and society. Most of the chapters have been written by scholars of repute who have spent their lifetime working on migration and the factors associated with it. This handbook is an attempt to address the lacunae in internal migration studies using both big data, such as Indian censuses, National Sample Surveys, India Human Development Surveys and Kerala Migration Surveys, and micro-level data collected by enthusiastic researchers in most parts of India to explore the unknown facets of internal migration. This book employs interdisciplinary and mixed methods to examine issues such as climate change, gender, urbanization, caste/tribe, religion, politics and emergence of migration policies. It addresses the crucial question as to why temporary and short-term migration continues to be an important livelihood strategy for millions of migrants thereby having an everlasting impact on the sociopolitical and economic structure of the country.